Closing the gap: The impact of the medicaid primary care rate increase on access and health - Diane Alexander; Molly Schnell (Federal Reserve Bank of Chicago, 2017)
The difficulties that Medicaid beneficiaries face accessing medical care are often attributed to the program's low reimbursement rates relative to other payers. There is little evidence, however, as to the actual effects of Medicaid doctor payment rates on access and health outcomes for beneficiaries. In this paper, we exploit within-state variation in Medicaid reimbursement rates primarily driven by the Medicaid fee bump - a provision of the Affordable Care Act mandating that states raise Medicaid payments to match Medicare rates for primary care visits for 2013 and 2014 - to quantify the impact of physician payment on access to treatment. As Medicaid rates are set by states and vary considerably in generosity, the policy had a large and heterogeneous impact across states. We find that increasing Medicaid payments to primary care doctors is associated with significant increases in doctors' visits, improvements in access measures, better self-reported health, and fewer school days missed among Medicaid beneficiaries.
Keywords: I11; I18; H51; H75; 330; Medicaid; primary care; access; physician reimbursement